Helminths parasitizing the digestive tract of Muridae captured in São Paulo County, state of São Paulo, Brazil: prevalence, parasitic intensity and importance to public health - Chieffi, Pedro Paulo (1980)
Between 1977 and 1979, 205 rats were autopsied. They had been cap tu red alive, in São Paulo Coun ty, to determine the prevalence and the intensity of parasitism by helminths in the digestive tract of rats. Besides, the importance of those rodents as reservoirs and disseminators of zoonotic h elmin thiases could be stressed. Thirteen helmin th species were identified and the prevalence of at least one species was 91.7%; of two to three species, 50%, whiJe 25% harbored four or more species, The prevalence and parasitic intensity were highest in the northern zone of the county and in adult rodents. Among the 13 species identified, six were zoonatic. Thus, rats may be reservoirs and disseminators of helrnin ths parasitic of man.